The Effectiveness of Using Code Switching in Teaching English on Higher Education - Dian Anggraini; Asma Alhusna; Vivi Nila Sari; Desi Andriani (Universitas of Muhammadiyah Makassar, 2023)
The occurence of using code switching in classroom appears for lecturer to explain topic, it also uses English-Indonesia, the students are difficult to understand when lecturer speaks English. The problem appears for students because of the difficulties to say something. This study aims to determine the factors that influence the use of code switching and the types of code switching used in learning English. The research method is descriptive qualitative. Collecting data by means of interviews, observations and video recordings. Data analysis is used to analyze information related to the use of code switching Indonesian English conversation. The participants of this study were two teachers who had experience of code switching while teaching. This study found five reasons teachers use code switching in teaching and learning English: discussing specific topics, making teaching and learning more practical, managing classes, building social relationships, and encouraging active student participation. From observations found three types of code switching used by teachers. The results showed that the use of code switching in learning English found 3 types of code switching, namely; (1) inter-sentential code switching occurred in 580 data (58%), (2) intra-sentential code switching occurred in 300 data (30%), and (3) Tag-code switching occurred in 127 data (12%). The factors behind the use of code switching in learning English are structural linguistic factors, internal psycholinguistic factors, and external social factors. The most dominant factor behind the occurrence of code switching is the structural linguistic factor, namely students do not master English. The teacher applies code switching to facilitate students to more easily understand the material being presented.